QUALIFICATIONS OF CLASS AND SOCIAL STUDIES TEACHERS RELATED TO DRAMA - Tekin ÇELİKKAYA; İhsan KOÇ (International Journal of Eurasia Social Sciences, 2015)
In this study, it is aimed to determine the qualifications of class and social studies teachers for the drama methods. The universe of this study includes 310 class teachers and 106 social studies teachers working in Kırşehir in 2011-2012 academic year. The sample research group includes 135 class teachers who teach 4th and 5th grade and 84 social studies teachers and in totals 219 teachers working for Kırşehir Directorate of National Education. "Competencies Regarding Drama Techniques" scale developed by researcher was used for collecting data. SPSS 15.00 program was used for the analysis of the data. As a result, The teachers have stated that they know about drama techniques, they know story-event visualization technique most and the Station Technique least; they use drama techniques little or never; they generally have information on the steps of the drama technique; they face difficulties in implementing the drama method due to exam anxiety most and the attitude of parents least.